Efektifitas Audio Afektif (Musik dan Narasi Emosional) terhadap Emosi pada Siswa SMP Yayasan Panti Asuhan Al Andalusia Pela Mampang - Abia Sharla; Dhaifina Nurina Idzni; Ilham Rifqi; Junia Nasela (JURNAL RISET RUMPUN ILMU KESEHATAN, 2024)
This study aimed to examine the effectiveness of affective audio consisting of music and emotional narration on emotional changes among junior high school students at Al-Andalusia Orphanage Foundation, Pela Mampang. Adolescence is a developmental period characterized by emotional fluctuations influenced by academic, social, and environmental demands, highlighting the need for simple and accessible emotional regulation interventions. This research employed a quasi-experimental method using a pretest–posttest control group design. A total of 30 junior high school students participated in the study and were randomly assigned to an experimental group (n = 15) and a control group (n = 15). The experimental group received affective audio exposure for 5–7 minutes, while the control group did not receive any treatment. Emotional states were measured using the Positive and Negative Affect Schedule (PANAS), which assesses positive and negative affect. Data were analyzed using a paired samples t-test. The results indicated a decrease in emotional scores in the experimental group after the intervention; however, the difference was not statistically significant (p > 0.05). Nevertheless, the effect size for the experimental group was in the moderate range, suggesting a meaningful practical effect of affective audio on students’ emotional states. These findings indicate that affective audio has potential as a light emotional intervention, although future studies with stronger methodological designs are recommended.